Effect of Cardiorespiratory Fitness on Academic Achievement is Stronger in High‐SES Elementary Schools Compared to Low. (10th September 2018) - Garber, Michael D.; Stanhope, Kaitlyn K.; Shah, Monica P.; Cheung, Patricia; Gazmararian, Julie A.
ABSTRACT: BACKGROUND: Academic achievement is influenced by factors at the student, school, and community levels. We estimated the effect of cardiorespiratory fitness performance on academic performance at the school level in Georgia elementary schools and examined effect modification by sociodemographic factors. METHODS: This study is a repeat cross‐sectional analysis of Georgia elementary schools between 2011 and 2014 (approximately 1138 schools per year). Multivariable beta regression estimated the effect of the proportion of 4th and 5th graders meeting cardiorespiratory fitness standards on the proportion of 5th graders passing standardized tests for Reading, English and Language Arts, Mathematics, Science, and Social Studies and considered potential interaction by school‐level socioeconomic status (SES), racial composition, and urbanity. RESULTS: There was a 0.15 higher estimated odds (OR: 1.15 (1.09, 1.22)) of passing the mathematics standardized test for every 10‐percentage‐point increase in school‐level cardiorespiratory fitness among high‐SES schools and 0.04 higher odds (OR: 1.04 (1.02, 1.05)) for low‐SES schools. This pattern was similar for other academic subjects. No effect modification by racial composition or urbanity was observed for any academic subject. CONCLUSIONS: Promoting physical fitness may be effective in improving academic performance among high‐SES schools, but additional strategies may be needed among lower‐SES schools.